CURRENT LEGAL SETTING AND FUTURE MARKET REGULATORY CHALLENGES OF SECURITIES MARKET IN THE REPUBLIC OF MACEDONIA - Andonov, Marko; Janevski, Zoran; Davitkovska, Elena; Majovski, Irina (Institute of Economics – Skopje, 2016)
The legal setting of the Macedonian capital market primarily reﬂects the Law on Securities and all the relevant bylaws. The aforementioned law was enacted in November 2005 and amended on several occasions. It is largely harmonized with the relevant EU Directives, as well as the standards and principles of the International Commissions on Securities (IOSCO). One objective of the paper is to depict and analyze the current legal and institutional setting of the domestic capital market. In this regard, all the signifcant aspects of the relevant regulations will be highlighted. At the same time, we will review the latest regulatory challenges in this area resulting from the development of two newly drafted laws, which are expected to shed a new positive momentum on the Macedonian legislation in this feld following their adoption and to contribute to the dynamic development of the domestic capital market. In this way, the paper will determine the degree of compliance of the said draft legislation with the relevant EU directives and regulations. We will finally draw conclusions from the legal analysis displayed in the paper.
Keywords: capital market; securities; regulation